A Genetic Algorithm Solution to Solve the Shortest Path Problem in OSPF and MPLS - Selvanathan, N.; Tee, Wee Jing (Malaysian Journal of Computer Science, 2003)
This paper explores the potential of using genetic algorithm to solve the shortest path problem in Open Shortest Path First (OSPF) and Multi-protocol Label Switching (MPLS). The most critical task for developing a genetic algorithm to this problem is how to encode a path in a graph into a chromosome. The proposed approach has been tested on ten randomly generated problems with different weights. The experimental results are very encouraging and the algorithm can find the optimum solution rapidly with high probability.